Determinants of Investment Interest of Generation Z Madiun Residency in the Sharia Capital Market - Prasaja, Mukti; Amrulloh, Amri; Cahyaningdyah, Permatasari; Auraria Natcwata, Lanuda (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2024)
This study aims to analyze the factors that affect investment in the Sharia Capital Market. The research variables used in this study include financial inclusion, environment, investment interest and fintech moderation. The research methodology used is quantitative research with a type of causality study which is to determine the cause and effect of the hypothesis that has been determined. The respondents used in the study were generation Z in Madiun using purposive sampling techniques. Data collection using a questionnaire that is structured using a Likert scale. The results of the study showed that the variable that had a significant effect on investment interest was environmental awareness, while financial inclusion had no effect. Furthermore, for Islamic Financial Inclusion on investment interest when mediated by fintech, it produces a higher value than the direct influence of financial inclusion variables on investment interest. And the environment awaraness towards investment interest when mediated by fintech produces a higher value than the direct influence of the variable environment awaraness on investment interest.